Long-term, repeated doses of intravenous autologous mesenchymal stem cells for a patient with Parkinson's disease: a case report - Vij, Ridhima; Prossin, Alan; Tripathy, Mallika; Kim, Hosu; Park, Hyeonggeun; Cheng, Thanh; Lotfi, Djamchid; Chang, Donna (Frontiers in Neurology, 2023)
Parkinson's disease (PD) is a neurodegenerative disease that involves the loss of dopaminergic neurons in the substantia nigra pars compacta of the basal ganglia. Clinically, patient presentation involves a combination of motor and non-motor symptoms characterized by progressive worsening over time and significant decreases in overall quality-of-life. Despite there being no fully restorative cure for PD, Mesenchymal Stem Cell (MSC) therapy offers promising therapeutic potential. Here, we report a case of a 77-year-old female, living with idiopathic Parkinson's Disease for over 17 years. The patient received multiple infusions of autologous Hope Biosciences adipose-derived MSCs (HB-adMSCs). A total of 26 infusion treatments of HB-adMSCs were administered over the course of 2 years that resulted in marked improvements in her typical Parkinsonian symptoms, as demonstrated by the decreases in her UPDRS (Unified Parkinson's Disease Rating Scale) scores. Changes in clinical scores mirrored concurrent changes in regional brain metabolism as quantified by FDG-PET (Fluorodeoxyglucose-Positron Emission Tomography), compared to baseline. Long-term, multiple infusions of HB-adMSCs were safely tolerated by the patient without any serious adverse events. Further research is needed to evaluate the safety and efficacy of HB-adMSC therapy for the treatment of PD patients.